2013
DOI: 10.1002/art.37895
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Shortened Telomere Length in Patients With Systemic Lupus Erythematosus

Abstract: Objective. Patients with systemic lupus erythematosus (SLE) have a higher rate of premature death compared to the general population, suggesting a phenotype of premature senescence in SLE. Telomere length can be used to assess overall biologic aging. This study was undertaken to address the hypothesis that patients with SLE have reduced telomere length.Methods. Telomere length was measured crosssectionally in whole blood from SLE patients and agematched healthy female controls, using real-time quantitative pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
0
28
1
1
Order By: Relevance
“…Studies have shown a significant decrease of telomere length in patients with cancer [38,39]. Inflammatory conditions such as rheumatoid arthritis and systemic lupus erythematosus have been shown to effect telomere length irrespective of the disease activity [40,41]. Therefore these conditions were excluded from telomere analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a significant decrease of telomere length in patients with cancer [38,39]. Inflammatory conditions such as rheumatoid arthritis and systemic lupus erythematosus have been shown to effect telomere length irrespective of the disease activity [40,41]. Therefore these conditions were excluded from telomere analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In various tissues and cell-subtypes, accelerated cell turnover is inversely associated with replicative senescence. In disorders involving accelerated oxidative injury and chronic immune system activation as the main manifestation, such as systemic lupus erythematosus,33 rheumatoid arthritis32 and systemic sclerosis,34 enhanced cell turnover and telomere erosion has been extensively described. Furthermore, we observed no significant TL difference in treated patients with gout compared with patients without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length diminishes physiologically by approximately 20% between 20 and 80 years of age [42]. It also diminishes in case of exposure to tobacco, pesticides and in numerous chronic illnesses [43][44][45]. There is no standard technique to measure telomere length.…”
Section: Telomere Lengthmentioning
confidence: 97%
“…La longueur des télomères diminue physiologiquement avec l'âge, d'environ 20 % entre 20 et 80 ans [42]. La longueur des télomères diminue aussi en cas d'exposition au tabac ou aux pesticides et dans de nombreuses maladies chroniques [43][44][45]. Il n'y a cependant pas de technique standardisée de mesure de la longueur des télomères.…”
Section: Longueur Des Télomèresunclassified